La integración cultural y social de inmigrantes latinoamericanos en España - Cabrera Pérez, Lidia (2016)
This work presents the results of an investigation that includes two differentiated studies. In the first study, we identify integration indicators of the foreign population in Spain, in other words we attempt to find out what makes foreign people feel as if they form part of the society in which they live and value and feel its culture as their own. Indicators related to legislation, employment, health, the education system, leisure and participation, and communications media were identified. In the second study, we attempt to find out, via these indicators, how integrated the Latin American population feels.